Wealth Inequality and Private Savings : The Case of Germany - Dao, Mai (IMF Working Papers; Working Paper ;, 2020)
This paper explores the interaction between corporate ownership concentration and private savings, and by extension, the current account balance in Germany. As high corporate savings largely reflected capital income accruing to wealthy households and increasingly retained in closely-held firms, the buildup of external imbalances in Germany has been accompanied by widening top income inequality, rising private savings and compressed consumption rates. Rising corporate profits in an environment of high business wealth concentration account for 90 percent of the rise in the private savings rate and a third of the increase in the German current account surplus over 1999-2016.